Axial stiffness of a rotating trunnion joint. (November 2015) - Feng, Sheng; Geng, Haipeng; Zhang, Bo; Yang, Lihua; Yu, Lie
A trunnion joint is modeled as a circular plate with two types of outer boundary conditions. One is clamped supported and the other is simply supported. Symmetrical bending deflection is produced when an external force acts on the inner side of the circular plate. The governing equations of the circular plate with these two kinds of boundary conditions are solved by using finite difference method, and the axial stiffness of the circular plate is obtained according to the relationship between the external force and the bending deflection of the circular plate. In order to verify the accuracy of the finite difference method, a finite element method was also given. The effects of rotational speed and the ratio of inner radius to outer radius of the circular plate on the axial stiffness are studied. It is shown that the rotational speed can significantly affect the axial stiffness of the trunnion joint for these two cases, especially for a lower ratio of inner radius to outer radius of the circular plate. The axial stiffness increases monotonically with the increase in rotational speed. More specifically, for a lower ratio of inner radius to outer radius of the circular plate, the axial stiffness with the simply supported boundary condition at high rotational speed is more than twice as much as the case without considering the rotational speed. Correspondingly, it is more than one and a half times for the clamped supported boundary condition.